Group evolution of Manikganj project : two case studies. - Bangladesh Rural Advancement Committee (Dhaka : Research and Evaluation Division, Bangladesh Rural Advancement Committee, 1984)
Case studies on the landless laborers under an integrated rural development project.
Keywords: BRAC (Bangladesh Rural Advancement Committee)